RIVER VALLEYS AS AN INDICATOR OF NEW TECTONIC MOVEMENTS (American Journal of Interdisciplinary Research and Development, 2022)
In this аrticle it was cleared base on local materials learning the peculiavitiy of new tectonic acts in developing the landscapes.